"Estudio de tres semillas oleginosas de producción local (Plukenetia volúbilis (Sacha inchi), sesamum indicum (Ajonjolí) y cucurbita pepo L (Zapallo pepo)) para la obtención de aceite comestible de grado alimentario" - Guerra Chóez, Kelvin Stain (2017)
This research project is focused on the study of local production of oilseeds for the production of oil for food, for this was raised as an Objective: To study the characteristics of three seeds (Plukenetia volúbilis (Sacha inchi), Sesamum Indicum (Ajonjolí) and Cucurbita pepo L (Zapallo pepo)) by applying two methods of removal for oil. The experimental design was a randomized complete block design with a factorial arrangement AxB and two repetitions, to compare: Factor (different oilseed) and Factor B (methods of extraction) and the effect by interacting the two factors, which made it possible to determine differences in the performance and physicochemical characteristics. To establish the effects between the levels of the treatments, the significance test was applied Tukey test (p<0.05). The data analysis was performed using the statistical package Statgraphics, to define quality parameters were performed various analyzes such as: acidity, humidity, density and pH. In addition, conducted a comprehensive analysis of fatty acids by Gas Chromatography. This research concludes that the different treatments meet the standards of oil of food grade vegetable oils, it also presents similar characteristics to other edible oils of good quality. The results indicated that the oil obtained from seeds of Sacha Inchi presented higher performance was 37.03%, in addition to best result in density and pH, and in terms of quality important aspects which should be addressed in future research. While the seed of pumpkin pepo presented better results in acidity and moisture. With regard to the results of the cluster analysis, the sacha inchi-mechanical treatment-r1 and the treatment palma showed a greater distance between them (67.373), and it also secured two major components that predominated in the three oils studied were the Ac. Lauric acid (C12:0 and C18:3 Alpha-linolenic acid (omega 3). Key words: Oil seeds, oil, extraction, fatty acid profile, yield.